2012
DOI: 10.1159/000342804
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Tea Consumption and the Risk of Bladder Cancer

Abstract: Objective: Previous studies on the association between tea consumption and bladder cancer risk have only illustrated contradictory results. The role of tea in bladder carcinogenesis still remains conflicting. In order to illustrate the potential relationship between tea consumption and bladder cancer, a meta-analysis of case-control and cohort studies was conducted. Methods: Eligible studies were retrieved via both computerized searches and review of references. Stratified analyses on types of tea, gender, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 91 publications
(135 reference statements)
2
19
0
Order By: Relevance
“…In addition, several cell-based studies support such anti-cancer effects of GTP in BC (21,22). However, the anti-cancer effects of green tea consumption were controversial in epidemiological studies (8,12,13). Based on these facts, we speculated that something decreased the anti-cancer effects of green tea in BC patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, several cell-based studies support such anti-cancer effects of GTP in BC (21,22). However, the anti-cancer effects of green tea consumption were controversial in epidemiological studies (8,12,13). Based on these facts, we speculated that something decreased the anti-cancer effects of green tea in BC patients.…”
Section: Discussionmentioning
confidence: 88%
“…In bladder cancer, controversy persists regarding the relationships between green tea consumption and the risk of cancer, prevention of progression, and prolongation of survival. Briefly, although one study reported that green tea consumption significantly suppressed the risk of bladder cancer (12), several investigators showed that green tea consumption was not associated with such malignant potential (8,13). In addition, one study reported that green tea consumption increased the risk of BC (14).…”
mentioning
confidence: 99%
“…A comparison of the associations found between studies is challenging because of the heterogeneity in study types, populations and cancer types investigated. Traditional meta-analyses (Seely et al, 2005;Sun et al, 2006aSun et al, , 2006bZhou et al, 2007Zhou et al, , 2008Arts, 2008;Myung et al, 2009;Zhang et al, 2010;Fon Sing et al, 2011;Zheng et al, 2011Zheng et al, , 2012Sasazuki et al, 2012;Wang et al, 2012Wang et al, , 2013Genkinger et al, 2012;Qin et al, 2012;Wu et al, 2013) have principally focused on the differences in the risk of cancer between high tea consumers, low tea consumers and nonconsumers, or investigated tea consumption with respect to a specific cancer type. However, the tea consumption ranges and category cut-off values differ between studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tea consumption ranges and category cut-off values differ between studies. Another limitation of previous meta-analyses (Seely et al, 2005;Sun et al, 2006aSun et al, , 2006bZhou et al, 2007Zhou et al, , 2008Arts, 2008;Myung et al, 2009;Fon Sing et al, 2011;Zheng et al, 2011Zheng et al, , 2012Genkinger et al, 2012;Qin et al, 2012;Sasazuki et al, 2012;Wang et al, 2013;Wu et al, 2013) is the inclusion of retrospective case-control studies, which are sensitive to confounding factors and bias, especially recall bias. In the present study, we used uniform methods and definitions to perform a systematic review and meta-analysis of previously carried out prospective observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent metaanalysis 20 found that only the variety of green tea is associated with statistically significant lower risk with OR = 0.814 (95% CI: 0.678-0.976).…”
Section: Intake Of Coffee Alcohol Tea and Matementioning
confidence: 99%